Analisis Strategi Pemasaran Pada Percetakan Cipta Ratu - Anwar Fauzi Rohman; Syifa Pramudita Faddila (OPTIMAL Jurnal Ekonomi dan Manajemen, 2023)
Cipta Ratu printing is one of the printing businesses in the Karawang area, Cipta Ratu was founded in 2018 with high determination that this business is able to develop into a printing house that serves all printing needs for both the industrial segment and the general public. Cipta Ratu has a vision of becoming a printing company with a professional identity in every aspect of its business so that it becomes the mainstay of printing service users and has a mission to prioritize customer satisfaction. As the times progress, the Cipta Ratu company is faced with many similar companies that have appeared, making the Cipta Ratu printing press have to maintain its product position because industry competition is getting tougher, the conditions of intense competition are a problem faced by the Cipta Ratu printing press. The purpose of this research is to determine the marketing strategy for Cipta Ratu printing through SWOT analysis. In determining the marketing strategy it is necessary to know the internal factors of strengths and weaknesses, external factors of opportunities and threats. The strategy that can be implemented, namely the ST strategy, is a strategy that uses the strengths of the company to overcome threats or can be called a diversification strategy.